CRUMBLING PILLARS: HUMAN RIGHTS EROSION AMID EUROPE'S MIGRATION AND RULE-OF-LAW CRISES - J. Kovács, Sándor; Bień Węgłowska, I (Penerbit Lafadz Jaya, 2026)
Europe's human rights framework faces severe challenges from migration crises and rule-of-law backsliding despite robust ECHR and EU Charter protections. This doctrinal study analyzes 2020-2026 ECtHR/CJEU cases revealing systemic pushback violations (N.D. v. Spain), judicial purges in Hungary/Poland (Xero Flor v. Poland), and 5,800 execution backlogs. EU Migration Pact externalization and Article 7 sanctions (€137B frozen) show limited compliance amid political vetoes. Findings confirm judicial efficacy (1,326 judgments/€92M awards 2024) against enforcement fragility (70% execution rate). Public support (77% corporate accountability) contrasts policy inertia. Recommendations: automatic GDP sanctions, EU ECHR accession, empowered NHRIs. Without reforms, Article 2 TEU values risk erosion by 2030.